The Effectiveness of Library Digitization in Increasing Students' Reading Interest at MAN 1 Medan - Tanjung, Laila Ali; Mesiono, Mesiono (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Libraries play an important role in increasing students' reading interest. Digitalization expands access and attracts the interest of the younger generation, although challenges in accessing technology still exist. Evaluation of the effectiveness of digitization is necessary. The role of teachers, parents, and collaboration between libraries, schools, families, and government support is crucial for optimally supporting literacy development. The digital library at MAN 1 Medan shows that digital library services play an important role in increasing students' reading interest. The effectiveness and accessibility of the digital library, as well as the factors influencing its use, significantly contribute to the increase in students' reading interest. The digitization of the library at MAN 1 Medan significantly enhances students' reading interest. The research uses a qualitative approach with methods such as literature study, interviews, observations, and documentation from students, teachers, and librarians. Data is analyzed through reduction, presentation, and conclusion drawing, and its validity is tested through triangulation. The research results are expected to provide a clear picture of the effectiveness of library digitization and serve as a reference for future studies. The digital library implemented since 2024 aims to increase students' reading interest by providing access to a more diverse collection and digital applications. Digitalization is effective if supported by good implementation and the active role of teachers. Accessibility, ease of use, internet network quality, and the relevance of digital collections are important factors. Despite its great potential, digital libraries require more outreach, adequate infrastructure, and support from various parties to achieve optimal results.